Universities: a Geographer’s Point of View - Yakobson, Anatoly (project baikal, 2015)
Since the XIIIth century the number of universities in Europe has been constantly growing. During the XXth century similar growth was in the countries of the USSR, but its character changed. Until the 1950s universities appeared in big cities on a well-prepared staffing and organizational ground. In the last quarter of the XXth century there were tendencies towards inflation of the higher education, decrease of its prestige and its formalization. In the 1990s and up to the present time, bureaucratization of universities extended so much that it put the system of Russian universities on the edge of survival.
Keywords: Universities; geography; history; the XXth century; inflation of higher education